PENGARUH TINDAKAN KORUPSI TERHADAP KINERJA ORGANISASI SEKTOR PUBLIK - Agustiawan Agustiawan; Della Hilia Anriva (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
This research discusses corruption in the performance of public sector organizations. The purpose of this research is to examine corruption in the performance of public sector organizations. This research was conducted at the regional work unit (SKPD) in Pekanbaru as a sample. The analytical method used in this study uses a quantitative analysis. Hypothesis testing is carried out using the Structural Equation Modeling - Partial Least Square (SEM-PLS) approach using WarpPLS 3.0 software. The results of this study reveal that acts of corruption affect the performance of public sector organizations. This indicates that corruption that occurs in public sector organizations influences the performance of public sector organizations.